The Ribosome Biogenesis Protein Nol9 Is Essential for Definitive Hematopoiesis and Pancreas Morphogenesis in Zebrafish. - Ewa Bielczyk-Maczyńska; Laure Lam Hung; Lauren Ferreira; Tobias Fleischmann; Félix Weis; Antonio Fernández-Pevida; Steven A Harvey; Neha Wali; Alan J Warren; Inês Barroso; Derek L Stemple; Ana Cvejic (PLoS Genetics)
Ribosome biogenesis is a ubiquitous and essential process in cells. Defects in ribosome biogenesis and function result in a group of human disorders, collectively known as ribosomopathies. In this study, we describe a zebrafish mutant with a loss-of-function mutation in nol9, a gene that encodes a non-ribosomal protein involved in rRNA processing. nol9sa1022/sa1022 mutants have a defect in 28S rRNA processing. The nol9sa1022/sa1022 larvae display hypoplastic pancreas, liver and intestine and have decreased numbers of hematopoietic stem and progenitor cells (HSPCs), as well as definitive erythrocytes and lymphocytes. In addition, ultrastructural analysis revealed signs of pathological processes occurring in endothelial cells of the caudal vein, emphasizing the complexity of the phenotype observed in nol9sa1022/sa1022 larvae. We further show that both the pancreatic and hematopoietic deficiencies in nol9sa1022/sa1022 embryos were due to impaired cell proliferation of respective progenitor cells. Interestingly, genetic loss of Tp53 rescued the HSPCs but not the pancreatic defects. In contrast, activation of mRNA translation via the mTOR pathway by L-Leucine treatment did not revert the erythroid or pancreatic defects. Together, we present the nol9sa1022/sa1022 mutant, a novel zebrafish ribosomopathy model, which recapitulates key human disease characteristics. The use of this genetically tractable model will enhance our understanding of the tissue-specific mechanisms following impaired ribosome biogenesis in the context of an intact vertebrate.